Genetic diversity in ginger (Zingiber officinale Rose.) with reference to essential oil content - Rajan, P P Singh, V B Singh, H P Singh, S (Journal of Spices and Aromatic Crops, 2000)
D2 analysis was carried out on a set of 18 genotypes of ginger (Zingiber officinale) involving 8 metric traits, at Nagaland, lndia. The genotypes could be grouped into three clusters and while inter cluster D2 values ranged from 338.99 to 2029.63, intra cluster D’values ranged from 18.41 to 45.05. The major forces for divergence were rhizome yield per plant, oleoresin and fibre contents.